Stuff, sounds and stories: Musical and music-related things as life documents - Gonçalves, A. (16th Conference of the European Sociological Association: Tension, Trust, and Transformation, 2024)
The biographical research methods mainly focus on subjective accounts of lived experience and personal documents to dig out life trajectories and past events. Family photographs and other particular possessions are among the wide range of life data usually gathered by auto/biographical researchers. The prime task of this communication is to explore how biographical narratives constitute a unique process that evokes those and other materials that store and elicit lifetime memories. I am especially interested in understanding how musicians' life narratives are constructed around musical and music-related things and how that stuff is so complexly intertwined in their identities. All these issues will be discussed and illustrated through empirical cases taken from a recent research project conducted in Lisbon, Portugal, based on musicians' life and family (hi)stories. That research was enriched not only by documentation originating in the field (interviews, genealogies) but also by materials from the past (documentary films, vinyl and digital recordings), including the memorabilia safeguarded for generations (family photographs, historical recordings, collections of lyrics and music scores). Such a variety results from a few years of painstaking and patient work, counteracting the dispersion of sources.